FA-optimized fractional order PI control for bidirectional V2G and G2V systems with integrated subsystem management - Mohamed Shiek Mothi Ismail Mujupur; Mohamed Ismail Mohamed Mustafa (Institute of Advanced Engineering and Science, 2026)
This paper presents a Firefly algorithm (FA)-optimized, fractional order proportional-integral (FOPI), control strategy for bidirectional vehicle-togrid (V2G), and grid-to-vehicle (G2V) systems. The optimization focuses on minimizing key performance indices—integral of time-weighted absolute error (ITAE), integral of squared error (ISE), and integral of absolute error (IAE)—to achieve optimal dynamic response and energy efficiency. The control system incorporates converter with battery controller. The FA is employed to fine-tune the FOPI parameters, leveraging its robust global search capability to balance trade-offs between fast response, minimal overshoot, and stability. Simulation results validate the effectiveness of the proposed approach, demonstrating superior performance compared to conventional proportional–integral (PI) controllers, with ITAE reduced by 63.4% compared to PI controller. This study provides a scalable and efficient solution for advanced energy management in V2G/G2V systems, contributing to the sustainable integration of electric vehicles (EVs) with smart grids.